*The sensitivity of different types of mosquitoes and some natural enemies of the bio-pesticide mosquito larvae Bacillus thuringiensis israelensis - Saad Naji Al-abeady, Rukaya; M. Hilal, Saadi (Al-Qadisiyah Journal of Pure Science, 2018)
A series of laboratory experiments were conducted to assess the efficiency of different concentrations of Bacillus thuringensis var. israelensis and the Chitin synthesis inhibitor Applaud (buprofezin) in controlling larvae and pupae of the mosquito Cx.pipiens , in addition to study the effect of some biological and physical factors on the efficacy of the B. thuringensis var. israelensis. The results showed different water depth had also significantly effected the percentage of larvae mortility. Thus , when depth of water increased from 10 millimeter to 50 millimeter mortality percentage of 2nd larval instar decreased from 90% to 28.5% , but the 4th larval instar did not effected. Mortality percentage of 2nd larval instar of Cx.pipiens did not significantly affected when treated with B. thuringensis var. israelensis at different temperatures. Storage of stock solution of B. thuringensis var. israelensis for different periods of time had not resulted in any effect of its efficacy on larvae mortality of Cx.pipiens. The percentage of 4th larval instar mortality was increased from 2.5% to 15% as the concentration of B. thuringensis var. israelensis increased from 0.0875 mg./L. to 0.7 mg./L. after 24 hours from time of application.